A new strategy to fabricate nanoporous iron-based metallic glasses: Selective phase tailoring of amorphous-nanocrystalline composite alloys through electrochemical dissolution. (May 2017) - Jin, Yu; Li, Ran; Xu, Hongjie; Chen, Xiao-Bo; Zhang, Tao
Abstract: A feasible strategy was developed to fabricate nanoporous iron-based metallic glasses (npFe-MGs) by selective dissolution of the electrochemically active α-Fe nanocrystalline phase from Fe-Nb-B composite alloys. The yielded npFe-MGs exhibited a ligament size of 75 nm and a pore size of 120 nm. Morphology of the npFe-MGs ( i.e. pore size and pore number) could be tailored by the selection of precursor alloys prepared by varying rapid solidification conditions. Such a selective phase-tailoring approach provides new insights to the preparation of metallic glasses with promising nanoporous structure to satisfy a variety of engineering requirements, e.g. catalysis, microwave absorption, capacitor, etc . Graphical abstract: